Implementasi Sistem Informasi Manajemen sebagai Upaya Peningkatan Keunggulan Bersaing UMKM - Hakiki, Teguh Iman; Nasution, Muhammad Irwan Padli (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
This study seeks to investigate the application of Management Information Systems (MIS) development as a strategic tool to boost the competitive edge of Micro, Small, and Medium Enterprises (MSMEs) during the digital age. Swift technological progress demands that MSME operators adjust by adopting cohesive and streamlined information systems to bolster management activities and improve overall business performance. The research adopts a literature review methodology, scrutinizing pertinent academic materials on the subject. Results reveal that deploying MIS with embedded digital innovations like cloud computing, big data analytics, artificial intelligence, and the Internet of Things can enhance operational productivity, speed up information handling, and stimulate product creativity as a primary driver of market superiority. Despite this, obstacles such as inadequate human capital skills, substantial deployment expenses, and cybersecurity threats persist as significant hurdles. Consequently, advancing MIS alongside enhanced digital skills training, robust tech infrastructure backing, and flexible regulatory frameworks is crucial to enable MSMEs to endure and thrive in the competitive landscape of the digital economy.